Determining Extractive Contents Of Different Types Of - Ghazal, Mohammed Harith Mohammed (Universiti Sains Malaysia, 2017)
This research is done to determine extractive contents of different types of hard wood biomass and its effect particle size. The interaction between the type of biomass used and the different particle sizes with response to cellulose percentage is investigated and identified by using Design of experiment (DOE). There were three types of characterization done on the types of biomass sample, Scanning Electron Microscope (SEM) for morphology observation, X-Ray Diffraction (XRD) for crystallinity and Carbon Hydrogen Nitrogen Sulfur (CHNS) analyser to determine the carbon, hydrogen and nitrogen content. The characterization was done to identify and differentiate the differences between the different biomass and with different size ranges. The morphology study by SEM shows the difference in structure of the three different biomass sample with three different size range while the XRD shows the difference in crystallinity of each biomass sample with respect to their size range. A mathematical model was plot from the use of the ANOVA, by using the significance and interaction of the factors that was manipulated during the hydrolysis process of different biomass samples with different particle size range. From the results obtained, both type of biomass sample and particle size range shows little interaction with each other and it was found that type of biomass has a slightly higher significant factor to percentage of cellulose.